Public good or public bad? Indigenous institutions and the demand for public goods - Aldo Elizalde; Eduardo Hidalgo; Nayeli Salgado (Queen's University Centre for Economic History (QUCEH), 2023)
This paper argues that the underprovision of public goods can be partly explained by lower demand from Indigenous groups with high preferences for Indigenous identity and a high capacity for coordination. Examining the post-Mexican Revolution period (1920s-1950s), when the state used the first road network for nation-building, our diff-in-diff analysis shows that pre-colonial political centralisation is associated with less road infrastructure. This is attributed to stronger capacity for collective action and stronger Indigenous identity preferences. Finally, we show that poor road infrastructure today is linked to lower economic performance.
Keywords: H41; H79; N7; O18; 330; Indigenous institutions; public good provision; collective action; Indigenous identity